Repurchase Intention as the Impact of Service Quality and Atmosphere Store - Oktavian, Rizky Ferrari; Ummah, Nadiah Khoeru (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
In business, service quality and store atmosphere have a very important relationship, this is because when the service provided from a product or service is optimal in accordance with consumer expectations and supported by a good atmosphere, it will create a good company image in the minds of consumers. Service quality and store atmosphere can encourage consumers to make repeat purchases, this is because consumers who have received service according to their expectations and the atmosphere provided by the company provides comfort, consumers will feel happy with what they receive. This study aims to determine how the quality of service, store atmosphere, and repurchase interest at Delapan Belas Coffee And Beverages, Eatery. This study was conducted on consumers of Delapan Belas Coffee And Beverages, Eatery as a sample of 100 respondents by distributing questionnaires. The analysis method used is quantitative with descriptive and verification analysis. To process the data using Microsoft Excel 2019 and the SPSS 25 program for windows. The results of the study stated that the variables of service quality, store atmosphere, and repurchase interest are in the good category. The results also show that service quality has an impact on repurchase interest and store atmosphere has an impact on repurchase interest.